Indian Geographic Thought: A Critical Analysis of Traditional Knowledge System (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This paper presents a critical analysis of traditional knowledge systems in Indian geographic thought, exploring their development, key concepts, and contributions to our understanding of the world. The chapter examines the evolution of Indian geographic thought from ancient Vedic geography to classical Indian geography, highlighting the influence of folk geography and Puranic cosmography. It delves into key concepts such as desha (region), janapada (settlement), nagara (city), and prithvi (earth), which are central to Indian geographic thought. A critical analysis of these traditional knowledge systems reveals both strengths and weaknesses, including their impact on contemporary geographic thought. The chapter also explores the influence of colonialism and modernization on Indian geographic thought, leading to a decline in traditional knowledge systems. A comparative analysis with Western geographic thought highlights similarities and differences, demonstrating the significance of Indian thought in shaping global geographic understanding. This chapter argues that Indian geographic thought offers valuable insights into traditional knowledge systems, emphasizing the importance of understanding and appreciating indigenous perspectives. It underscores the relevance of Indian geographic thought in contemporary times, particularly in the context of sustainable development, environmental conservation, and cultural heritage. By examining the rich and diverse history of Indian geographic thought, this chapter contributes to a deeper understanding of traditional knowledge systems and their contributions to global geographic understanding.